A strong association of schizotypy with internalized stigma: the role of cognitive and emotional mediators - Patrick Raynal (Psychiatry Research Communications, 2025)
Schizotypy, encompassing cognitive-perceptual, interpersonal, and disorganized dimensions, is a significant risk factor for psychosis and associated functional impairments. Internalized stigma, involving the internalization of negative societal stereotypes about mental illness, contributes to psychological distress and hinders recovery. Despite the significant impact of internalized stigma on mental health, the relationship between schizotypy and internalized stigma remains unexplored. In this study, 502 university students completed assessments including the Schizotypal Personality Questionnaire-Brief and the Internalized Stigma of Mental Illness scale, alongside measures of repetitive negative thinking (RNT), social phobia, anxiety, and depression. Findings indicate that the higher levels of schizotypy are strongly associated with increased internalized stigma, with RNT and depression symptoms acting as significant mediators. Hierarchical regression analyses identified schizotypy as the strongest predictor of internalized stigma, surpassing social phobia and anxiety. These findings highlight the importance of addressing schizotypy and cognitive patterns like RNT in interventions aimed at reducing internalized stigma in individuals with high levels of schizotypy.